(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de J. G. Montes Cala, M. Sánchez Ortiz de Landaluce, R. J. Gallé Cejudo y T. Silva Sánchez, Studia Hellenistica Gaditana I. Teócrito, Arato, Argonáuticas Órficas, Cádiz, Universidad de Cádiz, 2003